Convexity-preserving using rational cubic spline interpolation - Karim, S.A.A. (Maxwell Science Publications, 2014)
This study is a continuation of our previous paper. The rational cubic spline with three parameters has been used to preserves the convexity of the data. The sufficient condition for rational interpolant to be convex on entire subinterval will be developed. The constraint will be on one of the parameter with data dependent meanwhile the other are free parameters and will determine the final shape of the convex curves. Several numerical results will be presented to test the capability of the proposed rational interpolant scheme. Comparisons with the existing scheme also have been done. From all numerical results, the new rational cubic spline interpolant gives satisfactory results. Â© Maxwell Scientific Organization, 2014.